2014
DOI: 10.1109/twc.2014.2340879
|View full text |Cite
|
Sign up to set email alerts
|

Resource Optimization in Device-to-Device Cellular Systems Using Time-Frequency Hopping

Abstract: Abstract-We develop a flexible and accurate framework for device-to-device (D2D) communication in the context of a conventional cellular network, which allows for time-frequency resources to be either shared or orthogonally partitioned between the two networks. Using stochastic geometry, we provide accurate expressions for SINR distributions and average rates, under an assumption of interference randomization via time and/or frequency hopping, for both dedicated and shared spectrum approaches. We obtain analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 41 publications
0
90
0
Order By: Relevance
“…Constraint (14e) captures the uplink resource contiguity constraint due to the SC-FDMA scheme for the links in cellular mode [14]. Constraint (14f) implies that the fraction θ of resources allocated to D2D-overlay must be at most equal to one, according to (8). Performanceprotection constraint (14g) captures the requirement that the minimum rate requirement, R i,min , has to be met for each link i ∈ C associated with a guaranteed bit rate (GBR) of humantype services.…”
Section: B Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Constraint (14e) captures the uplink resource contiguity constraint due to the SC-FDMA scheme for the links in cellular mode [14]. Constraint (14f) implies that the fraction θ of resources allocated to D2D-overlay must be at most equal to one, according to (8). Performanceprotection constraint (14g) captures the requirement that the minimum rate requirement, R i,min , has to be met for each link i ∈ C associated with a guaranteed bit rate (GBR) of humantype services.…”
Section: B Problem Formulationmentioning
confidence: 99%
“…Sc ← Sc ∪ {i} 32: (8) allocation algorithm proposed in [14], the joint consideration of D2D-capable IEDs requires an efficient mechanism for a dynamic selection of the transmission mode and allocation of data resources with performance guarantees. We provide the details in the following.…”
Section: B Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the mobilities of devices and the complex interference effects, traditional static radio planning can prove to be difficult to apply, while statistical methods have recently been proven to yield useful insights [5]- [7]. In a recent study on multi-hop D2D [7], where BSs, CC UEs, and D2D UEs all conform to spatial Poisson Point Processes (PPPs) of different densities, it was found that statistically D2D sharing the uplink (UL) band performs much better than D2D sharing the downlink (DL) band in terms of outage probability.…”
Section: A D2d and CC Performance Trade-offmentioning
confidence: 99%
“…The majority of existing analysis is based either on simulation [1]- [3] or simple geometric abstractions [4]. Thus far, stochastic geometry based analysis has only considered a single-hop D2D scenario [5]. The more general scenario of multi-hop D2D with partner selection for routing in a particular direction has been neglected.…”
Section: Introductionmentioning
confidence: 99%